Toxic marine epiphytic dinoflagellates, Ostreopsis siamensis and Coolia monotis (Dinophyceae), in New Zealand - Lesley Rhodes; Janet Adamson; Toshiyuki Suzuki; Lyn Briggs; Ian Garthwaite (New Zealand Journal of Marine and Freshwater Research, 2000)
Ostreopsis siamensis and Coolia monotis (Ostreopsidaceae) are newly recognised additions to New Zealand's toxic marine microflora and occur epiphytically on seaweeds throughout subtropical New Zealand. O. siamensis “blooms” during summer, becoming freely motile; it tolerates temperatures of 15–25°C and salinities of 28–34 ppt. C. monotis also occurs in sediments in Nelson/ Marlborough and Stewart Island, at 10–30°C and salinities of 20–34 ppt. O. siamensis from Rangiputa, Northland, produced activity equivalent to ≤0.3 pg cell~’ of palytoxin as measured using a haemolysis‐neutralisation assay, and cell extracts killed mice by intraperitoneal injection. Extracts of oysters fed with O. siamensis did not kill mice. C. monotis , from Rangiputa, produced compounds in extracts of cells and of culture supernatant which were also toxic to mice and which are currently being characterised. C. monotis caused positive sodium channel activity in neuroblastoma assays; O. siamensis was cytotoxic, and irreversibly suppressed cell firing in hippocampal brain slices. Lectin probes differentiated the two species, suggesting differential sugar moieties at their cell surfaces.